Valve-Sparing Reimplantation Technique for Treatment of Neoaortic Root Dilatation Late after the Arterial Switch Operation: Raising the Bar - Liebrich, Markus; Scheid, Michael; Uhlemann, Frank; Hemmer, Wolfgang B. (The Thoracic and Cardiovascular Surgeon Reports, 2014)
Neoaortic root dilatation can develop during long-term follow-up after an arterial switch operation (ASO). Although few patients require surgical reintervention, significant valve regurgitation is still an important cause of late morbidity. We report on a 15-year-old boy with significant dilatation of the neoaortic root that was treated with the valve-sparing reimplantation technique. There is only one reported case of valve-preserving surgery late after the ASO. Valve preservation is believed to be superior to valve replacement in patients with aortic regurgitation due to better hemodynamic performance and avoidance of anticoagulation therapy.
Keywords: transposition of the great arteries; arterial switch operation; valve-sparing reimplantation technique